(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Background: It had been a general observation that the number of female patients undergoing SPECT myocardial perfusion imaging (MPI) is lower per week.This study was done to find out their proportionand association among their symptoms, history of (h/o) acute coronary syndrome (ACS) and corresponding myocardial perfusion. Patients and methods:This cross sectional retrospective study was conducted in 2017 on a group of patients who underwent gated SPECT myocardial perfusion imaging (GSMPI)from February 2005 to October 2016. Clinical record files and image files of all female patients were selected for analysis. The symptoms were retrospectively categorized according to New York Heart Association (NYHA) class while the patients were categorized according to their h/o ACS and myocardial perfusion in each patient was categorized as normal or perfusion defect. Data were analyzed using SPSS v.20. Results:Among 1347 patients undergoing GSMPI 196 (14.6%) were female with a 4.4-fold increase in number over 12 years. Mean age was 51.8 ± 10.1 (27-80). Symptom categorization assigned 84 patients in NYHA class I and 112 in NYHA class II. There was no h/o ACS in 143 while 53 had a previous h/o hospitalization due to ACS. GSMPI revealed normal perfusion in 156 patients with mean left ventricular ejection fraction (LVEF) of 66.6 ± 13.6. Perfusion defect was present in 40 patients with mean LVEF of 45.5 ± 15.8. NYHA class of symptoms was not associated with perfusion status (p > 0.05).H/o ACS was found to have association both with NYHA class of symptoms and with perfusions status (p < 0.05). Conclusions: Proportion of female patients undergoing GSMPI is low. Presence of perfusion defect in female was not associated with NYHA class of symptom. Bangladesh J. Nuclear Med. 22(2): 103-107, Jul 2019